2009 national winter canola variety trial - Stamm, Michael; La Barge, Cynthia (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Objectives of the National Winter Canola Variety Trial (NWCVT) are to evaluate the performance of released and experimental varieties, determine where these varieties are best adapted, and increase visibility of winter canola across the nation. Breeders, marketers, and producers use information collected from the trials. Over the past decade, the number of environments and entries tested have increased. The NWCVT is planted at locations in the Great Plains, Midwest, northern United States, and Southeast. The wide diversity of environments has improved our knowledge and understanding of winter canola variety performance.
Keywords: Canola; Kansas; Yield; Environmental factors; Oil